Effect of lattice potential upon the surface diffusion of Si on Si(100) - Ibrahim Ali , Noorbatcha; L.M, Raff; D.L, Thompson (American Institute of Physics (AIP), 1985)
The surfacediffusion of Si atoms on Si(100) is examined using three different lattice potentials suggested by Keating, by Weber, and by Baraff e t a l. Jump frequencies of Si atoms between adjacent adsorbtion sites are computed on each potential surface at 800, 1000, 1200, and 1500 K using classical trajectory methods. Diffusion coefficients are obtained directly from the jump frequencies and activation parameters from Arrhenius plots of the diffusion coefficients. The activation energy obtained in our previous calculations using Weber’s lattice potential is shown to be too small due to a lattice force field whose force constants are too large by about 25%. The best results are obtained with the Keating potential. This surface gives an activation energy of 7.47 kcal/mol for Si diffusion on Si(100). This result, coupled with the ratio of activation energies for Si(100) and Si(111) surfaces obtained in our previous studies, suggests an activation energy of 5.25 kcal/mol for Si diffusion on Si(111). This is in very good accord with the measured value of 4.6 kcal/mol obtained in ultrahigh vacuum deposition of silicon.